2021
DOI: 10.3390/cells10102532
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding the Direct and Indirect Actions of Growth Hormone in Controlling Hepatocyte Carbohydrate and Lipid Metabolism

Abstract: Growth hormone (GH) is critical for achieving normal structural growth. In addition, GH plays an important role in regulating metabolic function. GH acts through its GH receptor (GHR) to modulate the production and function of insulin-like growth factor 1 (IGF1) and insulin. GH, IGF1, and insulin act on multiple tissues to coordinate metabolic control in a context-specific manner. This review will specifically focus on our current understanding of the direct and indirect actions of GH to control liver (hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 218 publications
(286 reference statements)
0
11
0
Order By: Relevance
“…It is well established that a reduction of GH signaling is associated with liver steatosis and development of non-alcoholic steatohepatitis, both in humans and in mouse models, and increasing GH signaling can improve fatty liver endpoints (52,53). However, we found that treatment with a high dose of AAV8-STAT5 CA resulted in certain histopathological changes indicative of liver injury that cannot be attributed to the AAV8 infection per se , as they were not seen in AAV-Luciferase controls.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that a reduction of GH signaling is associated with liver steatosis and development of non-alcoholic steatohepatitis, both in humans and in mouse models, and increasing GH signaling can improve fatty liver endpoints (52,53). However, we found that treatment with a high dose of AAV8-STAT5 CA resulted in certain histopathological changes indicative of liver injury that cannot be attributed to the AAV8 infection per se , as they were not seen in AAV-Luciferase controls.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence showing that GH reduces the DNL of adipose tissue [ 154 ], leading to significant fat mass loss. In the context of nutrient deprivation such as fasting and Type I diabetes, circulating insulin and IGF1 levels are reduced [ 155 ], while the fasting-induced rise in GH promotes white adipose tissue (WAT) lipolysis [ 156 ]. Additionally, the promotion of GH is not through a STAT5-dependent mechanism.…”
Section: Growth Hormonesmentioning
confidence: 99%
“…For mice with specific knockout of STAT5 in adipocytes under chow-fed conditions, whose JAK-STAT signal pathway is dysregulated, increased adipose tissue mass will develop and improve body insulin sensitivity [ 159 ]. However, the loss of adipocyte STAT5 is neither associated with a reduction in WAT lipolysis nor does it impact the ability of GH treatment to reduce WAT mass [ 155 ]. These results suggested that WAT mass is affected by GH/GHR signaling in a STAT5-independent manner.…”
Section: Growth Hormonesmentioning
confidence: 99%
“…The liver is a central metabolic organ, but also plays an important immunological role, serving to maintain tolerance under homeostatic conditions [ 1 , 2 , 3 ]. The liver is comprised of hepatocytes, which make up approximately two thirds of its total cell population and exert largely metabolic functions, comprising the synthesis of numerous types of plasma proteins—for example, albumin [ 4 ], fatty acids [ 5 ], carbohydrates [ 6 ], and bile acid metabolism [ 7 ]—but are also pivotal for detoxification [ 8 ]. The heterogeneous group of non-parenchymal cells (NPCs) plays an important role in immune regulation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%